Portrayals and Appraisals of Puritans and Puritanism - Drozdowicz, Zbigniew (Humaniora. Czasopismo Internetowe, 2020)
The aim of these deliberations is to introduce several substantially dissimilar portrayals of Puritans and Puritanism and assessments of their achievement, as well as point to at least some of the sources and circumstances from which the differences stemmed. A proportion of these discrepancies arise from a religious background, while others are rooted in non-religious factors. Still, these are not the only elements to shed light on the objectivity or its absence among the authors of those portrayals and appraisals, as interesting insights may also be obtained from the varied temporal perspectives they adopted and the references to such distinct locations where Puritans functioned as sixteenth- and seventeenth century England and America.